WHO ARE THE TOURISTS SHARING CONTENT ON SOCIAL MEDIA? BEHAVIOUR AND CHARACTERISTICS - Antunes, Nuno M.B.; Ramos, Célia M.Q.; Sousa, Carlos M.R. (Journal of Tourism, Sustainability and Well-being, 2018)
Increasingly, tourist information on the Internet comes from the content generated by users, being no longer limited to the communications of tourism professionals and government entities. At the same time, the comments, opinions and reviews made by consumers are the type of information which tourists value the most. This reality means that the Internet has become an extremely valuable source of information for prospective travelers. This study aims to identify and characterize the behavior patterns of tourists on social media during and after their travels, specifically: who are the tourists who create content, what leads them to have this initiative, and what behaviors stand out on each of these platforms. The methodology is based on a questionnaire survey, which was applied to tourists. The data was analyzed using descriptive statistical methods, cluster analysis and principal component analysis. It is possible to categorize tourists according to three perspectives regarding use of social media during and after the trip: those who prefer review websites, those who prefer social networks and those who don’t particularly use social media in general.